PRELIMINARY RESULTS OF ARCHAEOLOGICAL RESEARCH THE WESTERN GATE OF THE MEDIEVAL SETTLEMENT DZHANKENT IN 2018 (Journal of history, 2019)
The article highlights some of the results of the archaeological study of the defensive structures of the medieval hillfort of Dzhankent, located in Kazaly district, Kyzylorda region. According to medieval eastern sources, the mound in the last period of its existence functioned as the capital of the Oguz state in the lower reaches of the Syr Darya. The article describes the features of the planigraphy of the main entrance gate of the ancient hillfort Dzhankent. The preliminary results of field archaeological research at the main entrance gates of the monument show that, during the erection of the fortress walls, the construction techniques of the neighboring region in the Lower Amudarya were used, which confirm the features of the Dzhankent building structures that have similar architectural traditions of the urban culture of Central Asia. His closest analogies are the design of Dzhankent in Khorezm. First of all, it is the hillfort of Toprak-Kala, which gives the closest analogies for Dzhankent on the internal layout and location of the Citadel. And although Toprak-Kala dates from an earlier period, the comparison of the planning features of the two monuments is quite legitimate, since it is obvious that the spatial-planning model used in the late re-planning of Dzhankent was formed much earlier.